Personal, Social and Vocational Outcomes of Inclusive University for People With Intellectual Disability - O'Donovan, Mary‐Ann; Wedgwood, Nikki; Westermann, Greta; Rillotta, Fiona; Aitken, Tess (Journal of intellectual disability research, 2025)
ABSTRACT Background Though people with intellectual disability have historically been excluded from university education, over the past three decades programmes facilitating the inclusion of people with intellectual disability in higher education, including university, have been developed in some jurisdictions such as the United States, Canada, Ireland, Europe and Australia. There is limited examination of the full range of potential outcomes for students with intellectual disability participating in such programmes. Such research rarely explores barriers and facilitators in relation to particular programme models and the achievement of the potential outcomes. The current study set out to examine the range of outcomes associated with inclusive university programmes, with a particular focus on autonomy, self‐confidence, inclusion and employment. Method For this scoping review, six academic databases were searched using broad search terms. Forty‐five studies meeting our inclusion criteria were subjected to quality assessment to ensure only high‐quality evidence informed data analysis. Twenty‐two studies were included in the final review, from which data were extracted to answer our research question. Results Students were reported to achieve outcomes related to employment, confidence, autonomy and social skills. Factors reported as either facilitating or impeding positive personal, vocational and/or socio‐emotional outcomes for students with intellectual disability participating in inclusive university programmes included accessibility, expectations, supports, attitudes and acceptance, pedagogy and programme design. Conclusions Programmes that provide individualised support for the inclusion of people with intellectual disability in university life led to primarily positive outcomes for people with intellectual disability. We argue that a whole‐of‐university approach to supporting full and genuine inclusion of students with intellectual disability is needed and we provide recommendations for research and practice.